Programmable musical bell / Nor ‘Aida Yusop and Shahida Yusof - Yusop, Nor ‘Aida; Yusof, Shahida (2003)
The circuit presented here is that of a musical bell which may be programmed for generation of a number of musical notes. To design this circuit we need to use 4 types of ICs, resistors, capacitors, transistors, speakers, port meters, switches and diodes. 1C1 (NE555) is a timer. Frequency of the timer IC may be varied with the help of portmeter VR1 The output of IC1 at the selected frequency of operation is coupled to the clock input of IC2 (CD4017). IC3 (CD 4051) is a C-MOS 8- input analogue multiplexer. Its function is to make electrical connection between output of IC3 and pin 15 of IC2. IC4 (CD 4060) is a 14-bit binary counter It is to produce the variety musical notes that can be heard through the speaker. The delay timer of tones is adjusted by port meter VR2.The transistor SL100 is use as amplifier. The 7-way rotary switches are used (SI, S2 and S3). The different music notes can be heard when the SI, S2, and S3 are taking to different position. The VR1 is used to change the tone. It can produce about 816 types of different musical notes